Examining the relationship between vocabulary knowledge and general English language proficiency / Nur Fatima Wahida Mohd Nasir, Nor Ashikin Ab Manan and Noraziah Azizan - Mohd Nasir, Nur Fatima Wahida; Ab Manan, Nor Ashikin; Azizan, Noraziah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2017)
The present study intended to examine the relationship between English language proficiency and receptive/ productive vocabulary knowledge of first year diploma students from a public university in Malaysia. The study was conducted among 136 students from the faculty of Architecture, Planning and Surveying to determine this relationship. The students’ receptive vocabulary knowledge was measured using Vocabulary Levels Test (VLT) Version 1 by Nation (1990) at 2000, 3000 and 5000-word levels while their productive vocabulary knowledge was measured using Lexical Frequency Profile (Laufer & Nation, 1995). The students’ grade for English subject in Sijil Pelajaran Malaysia (SPM) was used as the measure of general proficiency. It can be concluded from the results of regression analysis that more proficient learners have larger vocabulary repertoire which underscores the importance of vocabulary instruction. There is also adequate evidence to support that the students’ performance on VLT can be used as predictors of their general proficiency.